2014
DOI: 10.1589/jpts.26.1297
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Clinical Effects of Low-level Laser Therapy on Temporomandibular Joint Pain

Abstract: [Purpose] Temporomandibular joint (TMJ) pain is a symptom of TMJ disease. Low-level laser therapy (LLLT) is often used in the clinical treatment of TMJ pain. The aim of this study was to review the effective parameters of LLLT for TMJ pain. [Methods] This study was a systematic review in which electronic databases were searched for the period of January 2005 to January 2010. We selected reports of randomized controlled trials and calculated the effect size (ES) of the pain relief to evaluate the effect of LLLT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 20 publications
4
46
1
9
Order By: Relevance
“…Other recent research into treatment options for the management of TMD has included orthognathic surgery, 49 TMJ lavage, 50 physiotherapy, 51,52 low-level laser therapy, 53,54 exercise therapy, 55 pharmacological treatment, 56 and acupuncture. 57 However, results are mixed and generally unconvincing.…”
Section: Alternative Treatment Options For Tmdmentioning
confidence: 99%
“…Other recent research into treatment options for the management of TMD has included orthognathic surgery, 49 TMJ lavage, 50 physiotherapy, 51,52 low-level laser therapy, 53,54 exercise therapy, 55 pharmacological treatment, 56 and acupuncture. 57 However, results are mixed and generally unconvincing.…”
Section: Alternative Treatment Options For Tmdmentioning
confidence: 99%
“…It also suggested that nerve stimulation via LLLT occurs that changes the activity of the masticatory muscle . [19] The results of comparison between LLLT group and arthrocentesis group indicated superiority of arthrocentesis in pain reduction in the first two weeks, after that the result of both groups were close to each other as there was no statistical significant difference up to 6th month. The action of laser beam on joint capsule and synovial membrane as its dependent on cellular activity and metabolism that need a time to take part and raise to be significant, however the action of arthrocentesis is somewhat mechanical and physical action.…”
Section: Discussionmentioning
confidence: 71%
“…The low intensity laser therapy is a non-invasive modality and is used to promote relief of pain and tissue regeneration, promoting considerable comfort to the patient after application. (10,11,12,13) Pain decreased in both groups resulting in increased mouth opening.…”
Section: Discussionmentioning
confidence: 91%